PENGARUH OBESITAS PADA PERKEMBANGAN SISWA SEKOLAH DASAR DAN PENANGANANNYA DARI PIHAK SEKOLAH DAN KELUARGA - Labib Sajawandi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2015)
Obesitas didefinisikan sebagai suatu kelainan atau penyakit yang ditandai dengan penimbunan jaringan lemak tubuh secara berlebihan. Obesitas adalah permasalahan umum yang dialami anak-anak pada masa sekarang ini, tetapi tidak mendapat banyak perhatian karena dianggap hanya masalah fisik bukan masalah kognitif, padahal dampaknya dapat mengancam masa depan anak. Beberapa factor yang menyebabkan anak mengalami obesitas,diantaranya adalah: Factor genetic, Pola makan, Kurangnya aktifitas fisik, Factor psikologis, Factor keluarga, Factor social ekonomi, Factor psikososial, dan Factor kesehatan. Dampak Obesitas bukan hanya masalah fisik (seperti sakit-sakitan dan mudah lelah) tetapi juga psikis yang dapat mempengaruhi perkembangannya.Dalam memecahkan masalah obesitas ini, kita dapat merumuskan pola pemecahan masalahnya dari dua pihak, yaitu pihak sekolah dan keluarga. Kedua pihak ini harus bekerja sama saling mendukung untuk memecahkan masalah obesitas yang mengancam masa depan anak-anak mereka. Sekolah dan pihak keluarga terutama orang tua harus bisa mensosialisasikan dan mengimplementasikan pola makan sehat dan gaya hidup aktif untuk mengurangi dan mencegah obesitas sehingga dapat menyelamatkan masa depan anak-anak.Kata kunci: Obesitas, dampak fisik dan psikis, pola makan sehat, gaya hidup aktifObesity is defined abnormality or as a disease characterized by accumulation of excessive body fat. Obesity is a very common problem at the present time on children, but it did not get a lot of attention because look like just physical problem and not cognitive problems, whereas the impact can threatens future of children. Several factors that led children are obese: genetic factors,diet, lack of physical activity, psychological factors, family factors, social economic factors, psychosocial factors, and health factors. The impact of obesity is not only physical problems (such as sickly and easy tired) but also psychic that can affect on child development. In order to solve the problem of obesity, we can formulate the problem solving patterns of the two parties, the school and family. Both of sides Should Work together to support each other to solve the problem of obesity that threatening the Future of Their Kids. Schools and the Family especially parent Must socialize and Implementing Healthy Eating And Active Life style for Reduce and prevent obesity so it can save the Future of Children.Keywords: Obesity, Physical and psychological impact, Healthy Eating, Active Life styleObesity is defined abnormality or as a disease characterized by accumulation of excessive body fat. Obesity is a very common problem at the present time on children, but it did not get a lot of attention because look like just physical problem and not cognitive problems, whereas the impact can threatens future of children. Several factors that led children are obese: genetic factors,diet, lack of physical activity, psychological factors, family factors, social economic factors, psychosocial factors, and health factors. The impact of obesity is not only physical problems (such as sickly and easy tired) but also psychic that can affect on child development. In order to solve the problem of obesity, we can formulate the problem solving patterns of the two parties, the school and family. Both of sides Should Work together to support each other to solve the problem of obesity that threatening the Future of Their Kids. Schools and the Family especially parent Must socialize and Implementing Healthy Eating And Active Life style for Reduce and prevent obesity so it can save the Future of Children.Keywords: Obesity, Physical and psychological impact, Healthy Eating, Active Life style